2010
DOI: 10.1007/s00167-010-1264-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome using a ligament referencing technique in CAS versus conventional technique

Abstract: PurposeComputer-assisted surgery (CAS) for total knee arthroplasty (TKA) has become increasingly common over the last decade. There are several reports including meta-analyses that show improved alignment, but the clinical results do not differ. Most of these studies have used a bone referencing technique to size and position the prosthesis. The question arises whether CAS has a more pronounced effect on strict ligamentous referencing TKAs.MethodsWe performed a prospective cohort study comparing clinical outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 46 publications
3
22
0
1
Order By: Relevance
“…16 Many studies found no significant difference in satisfaction, pain or quality of life outcome; however, this conclusion is somewhat heterogeneously reported. 19,20 Neutral MA plays a very pivotal role in the success of longevity of an implant prosthesis and validates postsurgical clinical and functional outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…16 Many studies found no significant difference in satisfaction, pain or quality of life outcome; however, this conclusion is somewhat heterogeneously reported. 19,20 Neutral MA plays a very pivotal role in the success of longevity of an implant prosthesis and validates postsurgical clinical and functional outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…The usability and ease-of-use is still improvable and considered the prevailing limiting factor for mass acceptance [22, 34]. There is a learning curve the surgeon and the surgical team need to go through for each indication supported by navigation.…”
Section: Navigation For Orthopedic Surgerymentioning
confidence: 99%
“…However, Choong et al (Choong et al, 2009) reported patients that underwent navigation assisted surgery showed precise limb alignment (<3°), and concluded that accuracy improved new knee function and quality of life. Lehnen et al (Lehnen et al, 2010) reported, in a 1-year follow up study, that Western Ontario and McMaster University (WOMAC) scores and Knee Society scores of 43 navigation assisted surgery patients were notably higher than those of 122 patients that underwent conventional surgery. Patient satisfaction was 91% in the navigation assisted group, but only 70% in the conventional surgery group.…”
Section: Functional Resultsmentioning
confidence: 99%